Prevalence of extraarticular manifestations in rheumatoid arthritis and their relationship with serological status and disease severity - Mathkhor, Abdulsatar J. (International Journal of Advances in Medicine, 2022)
Background: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that attacks the synovial joints. It affects body systems, such as the skin, cardiovascular, respiratory systems, and other systems, which manifest as extraarticular manifestations. This study aimed to correlate RA with extraarticular manifestations and its relationship with serological status. Methods: One hundred fifty patients (30 male and 120 female) RA patients with a mean age of 49.9±11.9 attending the Rheumatology outpatient department and biological therapy center in Basrah Teaching Hospital were enrolled in the study and fulfilled the 2010 RA classification criteria of the American college of rheumatology/European league against rheumatism for RA. All the subjects underwent a thorough history, clinical examination, and laboratory investigations. Body mass index (BMI), the severity of pain using a visual analog scale (VAS) and disease activity using 28 joints (DAS28), and erythrocyte sedimentation rate were calculated for all patients. The relevant data were analyzed with appropriate statistical methods after 12 months. Results: The mean age, age at onset, disease duration, and BMI were 49.9±11.9, 41±2.1, 14.6±5.8, and 26.8±4.8 respectively. The disease onset was acute in 45 (30%) and insidious in 105 (70%) patients. Anemia, rheumatoid nodule, sicca syndrome, Felty syndrome, Sjogren syndrome, and joint erosions were more frequent in seropositive than seronegative patients. There is no difference in joint deformities between seropositive and seronegative patients. DAS28, VAS, ESR, and CRP were higher in patients with extraarticular manifestations. Conclusions: Extraarticular manifestations are significantly associated with seropositive disease and correlate to disease severity.